THE PRINCIPLE OF SUSTAINABLE DEVELOPMENT AND GOOD GOVERNANCE - Roy, Subir Kumar (Faculty of Law, Universitas Brawijaya, 2016)
Sustainable development leads the society towards a new orientation and hammers on our cognitive faculty to see the perspectives of development in a new form which requires the radical change in social economic and political perspectives and thus gives birth of sustainable governance. Environmental governance is a precise term indicates towards the activities of various institutions and structure of authority related to protection of natural environment. Environmental governance and the sustainable governance are not same. The former aims to involve government, individuals, industries, civil societies, Internationals and non-governmental institutes in policy formulations and decision making process in environmental performances to face the challenges of the globalised world and to curb pollutant. On the other hand governance for sustainability is value based and advocates for the preservation of integrity of ecology of the Earth.Â The approach of Sustainable governance is very specific and target oriented i.e. save the planate, promote human development and achieve universal prosperity and peace. But still we have not been able to achieve the above targets despite of having a number of conventions, treaties, and covenants etc. Furthermore the theme of â€˜green economyâ€™ of Rio+20 is a contested concept and the critiques apprehend that it may downplay the concept of sustainable development. Under the above backdrop this paper intends to scan the global initiative towards ensuring sustainable governance and will also make analysis that whether still the focus of the UN is pointed on sustainable governance or wandering in jugglery of brown and green economy.